2019
DOI: 10.1002/gps.5072
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of visual rating of posterior atrophy in predicting rapid cognitive decline in Alzheimer disease: A preliminary study

Abstract: Background Approximately 10% to 30% of Alzheimer disease (AD) patients progress rapidly in severity and become more dependent on caregivers. Although several studies have investigated whether imaging biomarkers such as medial temporal atrophy (MTA) and posterior atrophy (PA) are useful for predicting the rapid progression of AD, their results have been inconsistent. Objective The study aims to investigate the association of visually rated MTA and PA with rapid disease progression in AD. Methods This was a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…in AD. 33 Since CDT also taps into other cognitive domains such as planning and executive functions, 34,35 worse scores at baseline CDT might reflect a wider, albeit slight, multi-domain cognitive impairment in FAST rather than in SLOW decliners, as previously discussed. 4 The third independent predictor of FAST decline in our algorithm was plasma NfL: at baseline, higher plasma NfL levels were associated with an increased risk of FAST decline over time.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…in AD. 33 Since CDT also taps into other cognitive domains such as planning and executive functions, 34,35 worse scores at baseline CDT might reflect a wider, albeit slight, multi-domain cognitive impairment in FAST rather than in SLOW decliners, as previously discussed. 4 The third independent predictor of FAST decline in our algorithm was plasma NfL: at baseline, higher plasma NfL levels were associated with an increased risk of FAST decline over time.…”
Section: Discussionmentioning
confidence: 89%
“…Conversely, poor performances at CDT reflect an impairment of visuospatial skills, mainly relying upon the functioning of the parietal lobe, 30 which is involved early in the disease course 31 . Several connectivity studies have shown that the posterior network, including the posterior brain regions, was selectively impaired in AD 32 ; accordingly, posterior atrophy, mainly driven by parietal lobe atrophy, was demonstrated to be strongly associated with rapid cognitive decline in AD 33 . Since CDT also taps into other cognitive domains such as planning and executive functions, 34,35 worse scores at baseline CDT might reflect a wider, albeit slight, multi‐domain cognitive impairment in FAST rather than in SLOW decliners, as previously discussed 4 …”
Section: Discussionmentioning
confidence: 99%
“…In the current study, there was a trend for some cortical regions (left pars triangularis, P-value = 0.05, T-value = − 1.941; right posterior cingulate, P-value = 0.05, T-value = − 1.931), but they were not statistically significant. Considering the sample size of previous studies 53 55 , we attributed our findings on cortical thickness to the small sample size. However, with this sample size and statistical power, we identified additional associations between the WM T1w/T2w ratio and cognition and disease progression, which were not identified using cortical thickness values.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that APOE ɛ4 is a factor that slows cognitive decline in AD [33,34]. Moreover, atypical forms of AD with executive and language impairments [35] or with pronounced atrophy in the posterior cerebral area [36] have both been linked to more rapid decline. These characteristics were all observed in C2.…”
Section: Discussionmentioning
confidence: 99%